Arsen Rychinsky was my godfather - Payevskyi, Yu (Ukrai͏̈ns'ke relihijeznavstvo, 2007)
I am a person very far from the issues of religious studies. So I don't even know how to perform in front of such a solid audience. It turned out so much in my life that, as I see, a very famous person, even I did not know that she was so famous, Arsen Rychinsky was my godfather. The Rychinski family and the Pajewski family (this is my parents' last name) for many years, sometime in the 1920s, were as one family, that is, they were in very good relationship with each other, as much as in the good ones that I will give as an example . My father, Denis Pajewski, lived in Volyn as an emigrant from the Soviet Union: in the 1920s he fled to the West and then returned to Poland. He was, by profession, a businessman. When he raised start-up capital and wanted to start a business, he did not yet have Polish citizenship. Therefore, he opened his company by registering for Rychinsky. The fact is that in Poland there was a temporary center, that is, for so many years it was necessary to be a resident of this country in order to obtain the right to open a company.